Salvation stories: the rhetoric of story in sacred scripture - Briese, Llane B. (Gregorianum, 2025)
Pope Francis has observed that evangelizing communities encounter others "by word and deed" (Evangelii Gaudium, no. 24), echoing language from Dei Verbum and Luke-Acts that describes how revelation occurs within the historia salutis. This article explores the scope of this history of salvation, arguing that all history is narrative and that all narrative is rhetorical. Employing the scholarly tools of rhetorical narratology, the essay discusses how the salvation history recounted in Scripture persuades readers not only of truths, but also of goodness and beauty, leading to the conclusion that the same qualities that make biblical revelation persuasive also make the present-day transmission of divine revelation that occurs in evangelization effective. Biblical exegesis thus offers a model for discernment in the apostolate, as attention to narrative nuance promotes sensitivity to nuance in human relationships.